(untitled) (Journal of the College of Basic Education, 2023)
In this work the design, construction and testing of a photovoltaic-powered reverse-osmosis (PV-RO)desalination system is presented using Matlab. The system operates from seawater and requires no batteries, since the rate of production of freshwater varies throughout the day according to the available solar power. Initial testing of the system, with the modest solar resource available in Iraq, provided freshwater at approximately 1.5 m3/day. Nearer to the equator and with a PV array of only 2.4 kWP, a software model of the system predicts production of over 3 m3/day throughout the year. The system employs a Clark pump brine-stream energy recovery mechanism and this, coupled with variable water recovery ratio, achieves a specific energy consumption of less than 4 Three motors and pumps are employed and provide good energy and cost efficiency. Testing and modelling of the system components in MATLAB-Simulink is presented, together with a discussion of the full system modelling and design procedure, in which the aim was to minimise the cost of water